The economic burden of chronic obstructive pulmonary disease in the Asia-Pacific region : a systematic review - Woo, Lai Leng (2020)
Background: Chronic obstructive pulmonary disease (COPD) is a significant and disabling condition that entails high economic burden for society. Objective:The aim of this article is to assess cost studies of COPD and analyze cross-country cost comparisons in Asia-Pacific. Methods:A systematic literature search from October 2000 to October 2018 was conducted using PubMed, MEDLINE, and EMBASE to identify relevant studies. Costs reported by the different studies were converted to 2017 US dollars using the consumer price index for medical care. The quality of the studies was assessed using the Consolidated Health Economic Evaluation Reporting Standards.Results:Ten studies (6 countries and 11 estimates) were identified and included for full review after consideration of the inclusion and exclusion criteria. Annual total societal costs of COPD ranged from $4398 to $23 049 per capita in Japan and $453 to $12 167 in South Korea. There were no intracountry comparison estimates for the remaining countries (Singapore: $2700; Taiwan: $4000; China: $3942; and Thailand: $1105). In addition, there were estimates of partial costs in Singapore and Taiwan.Conclusions:Results of this review showed high cost variations between countries, with estimates in 2 countries (Japan and South Korea) exceeding those in UK and USA. Wide variation in disease cost estimates will continue to exist as long as there are differences in cost methodologies, disease severities included, and data limitation. We propose that researchers conducting burden-of-illness studies use standard methods and reporting formats to support cross-country comparisons.